Inflammatory bowel disease in the paediatric and adolescent age groups - a forgotten entity - De zoysa, M.I.M.; Samarasekera, D.N.; De Silva, M.V.C.; Dias, R. (My University, 2012)
Inflammatory bowel disease (IBD) is an uncommon disease in Sri Lanka but the prevalence appears to be increasing. However worldwide, it is still a rarity in the paediatric age group. Therefore in children it is often misdiagnosed or the diagnosis is often delayed until life threatening complications arise.